2009
DOI: 10.1111/j.1755-0998.2009.02628.x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of DNA barcoding into an ongoing inventory of complex tropical biodiversity

Abstract: Inventory of the caterpillars, their food plants and parasitoids began in 1978 for today's Area de Conservacion Guanacaste (ACG), in northwestern Costa Rica. This complex mosaic of 120 000 ha of conserved and regenerating dry, cloud and rain forest over 0-2000 m elevation contains at least 10 000 species of non-leaf-mining caterpillars used by more than 5000 species of parasitoids. Several hundred thousand specimens of ACG-reared adult Lepidoptera and parasitoids have been intensively and extensively studied m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
373
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 323 publications
(380 citation statements)
references
References 35 publications
4
373
2
1
Order By: Relevance
“…We gratefully acknowledge the team of ACG parataxonomists (Janzen et al 2009) who found and reared the specimens used in this study, and the team of biodiversity managers who keep alive the ACG forests that host these sawflies. The study has been supported by U.S. National Science Foundation grants BSR 9024770 and DEB 9306296, 9400829, 9705072, 0072730, 0515699, and grants from the Wege Foundation, International Conservation Fund of Canada, Jessie B. Cox Charitable Trust, Blue Moon Fund, Guanacaste Dry Forest Conservation Fund, Area de Conservación Guanacaste, and University of Pennsylvania (DHJ).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…We gratefully acknowledge the team of ACG parataxonomists (Janzen et al 2009) who found and reared the specimens used in this study, and the team of biodiversity managers who keep alive the ACG forests that host these sawflies. The study has been supported by U.S. National Science Foundation grants BSR 9024770 and DEB 9306296, 9400829, 9705072, 0072730, 0515699, and grants from the Wege Foundation, International Conservation Fund of Canada, Jessie B. Cox Charitable Trust, Blue Moon Fund, Guanacaste Dry Forest Conservation Fund, Area de Conservación Guanacaste, and University of Pennsylvania (DHJ).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Recent reviews of the state of development of barcoding include Waugh DNA barcoding provides an important tool to improve the quality or speed of floral and faunal studies, while, at the same time, such studies contribute to development of the global sequence library that is becoming an important community resource. The large-scale inventory of caterpillars, their hosts and their parasites in Costa Rica has provided an excellent example of how barcoding has changed the basic approach to an inventory project, starting with sampling, processing, identification, analysis, and even changing the approach to publication of results (Janzen et al, 2009; Hallwachs 2011a, 2011b; see also Strutzenberger et al, 2010). In addition to the changes in work flow there have been significant impacts, from finding cryptic species to matching dimorphic males and females, which have substantially improved the quality and depth of the inventory, but also greatly multiplied the number of situations requiring further taxonomic work for resolu- (Kress et al, 2009(Kress et al, , 2010Costion et al, 2011).…”
Section: The Present Status Of Dna Barcodingmentioning
confidence: 99%
“…The large-scale inventory of caterpillars, their hosts and their parasites in Costa Rica has provided an excellent example of how barcoding has changed the basic approach to an inventory project, starting with sampling, processing, identification, analysis, and even changing the approach to publication of results (Janzen et al, 2009;Hallwachs 2011a, 2011b; see also Strutzenberger et al, 2010). In addition to the changes in work flow there have been significant impacts, from finding cryptic species to matching dimorphic males and females, which have substantially improved the quality and depth of the inventory, but also greatly multiplied the number of situations requiring further taxonomic work for resolution.…”
Section: How Does Barcoding Change the Approach To An Inventory?mentioning
confidence: 99%
See 1 more Smart Citation
“…DNA barcoding uses a short standardized region of the mitochondrial gene cytochrome c oxidase (COI) as a key character for species-level identification and discovery (Floyd et al 2002;Hebert et al 2003a;Hebert et al 2003b;Janzen et al 2009;Smith et al 2006;Smith et al 2007;Smith et al 2008). DNA barcoding has been extensively used in biodiversity and taxonomic studies of Microgastrinae during the past few years (summarized in Fernández-Triana et al 2014), due to the recent availability of over 20,000 sequences from more than 75 countries (e.g., Smith et al 2013).…”
Section: Introductionmentioning
confidence: 99%